Konsep Otoritas dan Otoritarianisme Penafsiran Khâled M. Abou el-Fadl - Fakhruddin Fajrul Islam (INSTITUT AGAMA ISLAM BANI FATTAH (IAIBAFA), 2016)
Today, the anxiety of the authorities in the name of religion is an issue of interest to the talk. This is due to increasingly widespread and growing ideology of fundamentalism in the Islamic world. As an academic who is very familiar with Islamic law, Abou al-Fadl admitted that Islamic law is the heart and core of the Islamic religion. However Abou al-Fadl just do not believe that the intellectual treasures were able to survive the onslaught of the trauma of colonialism and modernity. Even thought, the remnants of the treasures of classical Islamic law is on the brink of extinction. Rests on the idea, he wanted to ‘revive’ the tradition of classical Islamic law is quite dynamic, and has a base that is tolerant and pluralistic epistemology. If Mohammed Arkoun claims, that in Islamic thought, there is still something ‘thoughtless’, then, Abou el-Fadl want re-formulation of the treasures of Islamic thought, namely ‘something that has been forgotten’.